Extracellular HMGB1 Contributes to the Chronic Cardiac Allograft Vasculopathy/Fibrosis by Modulating TGF-β1 Signaling - Zou, Huijuan; Ming, Bingxia; Li, Jun; Xiao, Yifan; Lai, Lin; Gao, Ming; Xu, Yong; Tan, Zheng; Gong, Feili; Zheng, Fang (Frontiers in Immunology, 2021)
Cardiac allograft vasculopathy (CAV) charactered with aberrant remodeling and fibrosis usually leads to the loss of graft after heart transplantation. Our previous work has reported that extracellular high-mobility group box 1 (HMGB1) participated in the CAV progression via promoting inflammatory cells infiltration and immune damage. The aim of this study was to investigate the involvement of HMGB1 in the pathogenesis of CAV/fibrosis and potential mechanisms using a chronic cardiac rejection model in mice. We found high levels of transforming growth factor (TGF)-β1 in cardiac allografts after transplantation. Treatment with HMGB1 neutralizing antibody markedly prolonged the allograft survival accompanied by attenuated fibrosis of cardiac allograft, decreased fibroblasts-to-myofibroblasts conversion, and reduced synthesis and release of TGF-β1. In addition, recombinant HMGB1 stimulation promoted release of active TGF-β1 from cardiac fibroblasts and macrophages in vitro, and subsequent phosphorylation of Smad2 and Smad3 which were the downstream of TGF-β1 signaling. These data indicate that HMGB1 contributes to the CAV/fibrosis via promoting the activation of TGF-β1/Smad signaling. Targeting HMGB1 might become a new therapeutic strategy for inhibiting cardiac allograft fibrosis and dysfunction.